UPAYA PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN NGETREP PADA MATERI NORMA DALAM KEHIDUPANKU DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA PANORAMA (PAPAN NORMA) - Dwi Miranda, Febiola; Nuzul Dui Charisma, Pinkan; Nabilatun Ni'mah, Azza; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of fifth grade students of SDN Ngetrep in Pancasila Education subject of Norms in My Life through the application of Problem Based Learning (PBL) learning model assisted by panorama media (norm board). The background of this research is based on the low student learning outcomes, understanding of norms, and limitations of learning media used by teachers. The method used was Classroom Action Research with cycles, involving 10 students as subjects. Data collection instruments included observation, tests, interviews, and documentation. The results showed that the application of the PBL model assisted by the norm board media was able to significantly improve student learning outcomes. At the pre-cycle stage, only 20% of students were complete, with an average score of 59. After the implementation of actions in cycle I, the level of completeness increased to 90% with an average score of 91. This result shows that the use of PBL model and norm board media is effective in improving students' learning outcomes in learning Pancasila Education.